The effects of kindergarden fees on the labour market participation of women with children - Zangerl, Felix; Pham, Isabel (Momentum Quarterly, 2020)
The presented analysis investigates how eliminated kindergarden fees influence the labour market participation of women with children under the age of six. The elimination of kindergarden fees in Vienna in autumn 2009 represents the initial motivation for the policy analysis. We conduct a “difference in differences” estimation by comparing Vienna to other similar urban areas in Austria, where the year before (2008) and after (2010) the policy change constitutes the time frame of analysis. We try to explain the extend of women’s weekly working hours through various socioeconomic factors recorded in the Mikrozensus survey. As childcare only partially explains female labour market participation which is determined by many more (un)observed factors, we cannot claim that the empirical analysis of the fees’ influence on female labour market participation yields significant effects.